Schwierige Therapieentscheidungen bei Schlaganfall und Demenz – Aspekte bei schweren vaskulären und fortgeschrittenen degenerativen Hirnerkrankungen - Guldner, Jürgen (DMW - Deutsche Medizinische Wochenschrift, 2020)
Severe stroke and neurodegenerative diseases often cause limitations in communication and willing capability. Decision processes in these conditions assume primarily a positive medical indication for any intervention. If not obtainable from an individual by itself, by a disposal or by a legal custodian, the presumed will of a patient has to be detected carefully. Evidence can be raised by an interview of relatives or an individual case discussion in a local ethical comitee. Stroke and dementia can raise the need for palliative care, especially a sufficient analgesia as well as other severe illnesses. Pain in demented persons is often underrated and undertreated. The diagnosis of dementia alone does not limit the indication for curative therapy in general. Ethical comitees or ethical visits are helpful instruments to find out an adequate decision in difficult situations.
Keywords: Schlaganfall; Demenz; Entscheidungsfindung; Palliativmedizin